Tectonics of Nisyros Island, Greece, by field and offshore data, and analogue modelling - Tibaldi, A.; Pasquarθ, F. A.; Papanikolaou, D.; Nomikou, P. (Journal of Structural Geology, 2008)
We use new on-land and offshore structural data and scaled analogue models to analyse the fault tectonic pattern at Nisyros Island (Greece), which has an active caldera that shows a complicated network of faults, fractures and volcano-tectonic structures. We measured 157 faults that show dominant dip-slip normal motions along planes mainly striking NE-SW, NNE-SSW, and NNW-SSE. Inside the caldera, dykes, necks and morphometric parameters of volcanic domes, explosion craters and fumarole pits indicate the control by NE-striking discontinuities on magma and gas paths. The NNW- and NE-striking faults bound a major block that underwent repeated downthrow and uplift movements during the late Pleistocene-Holocene. Experiments with scaled models of caldera resurgence and two magma chambers indicate the formation of an hourglass-shaped fault pattern, as seen in plan view, with an asymmetric increase in the fault offset and a widening of the fault divergence towards the volcano flank. All these data suggest that regional fault tectonics and stress state strongly guided magma upwelling and the emplacement of volcanic centres, whereas periodical bulging due to the overpressure of a second magma chamber located northwest of the caldera combined with faulting due to tectonic stresses, can account for the overall deformation field.
Keywords: Analogue modelling; Caldera; Faults; Nisyros; tectonics